Удосконалений спосіб отримання заморожених ягідних напівфабрикатів - Сімахіна, Галина Олександрівна; Науменко, Наталія Валентинівна (My University, 2020)
Мінімізації втрат аскорбінової кислоти при заморожуванні та зберіганні ягід можна досягти за допомогою методів кріопротекції. Мета досліджень — установити вплив різних кріопротекторів на мінімізацію втрат аскорбінової кислоти при замо-рожуванні та зберіганні ягід. Досліджувались ягоди чорної смородини, калини та журавлини у свіжому, заморо-женому, дефростованому станах. Заморожування ягід традиційним способом під-твердило відомий факт щодо істотних втрат аскорбінової кислоти. Вони склали у всіх видах замороженої продукції від 16,8 до 26,3%, а дефростованої — від 55,6 до 71%. Це є результатом кріоушкодження клітин ягід утвореними кристалами льо-ду, що призводить до окислення аскорбінової кислоти оксидоредуктазами та її втратіз клітинним соком при дефростації ягід. Реалізація теоретичних знань із вивчення кріопротекторів у кріобіології показала позитивний ефект кріопротекції при заморожуванні ягід. /Minimization of ascorbic acid losses during freezing and fro-zen storage of berries can be achieved by various methods of cryo-protection. The objectives of this research are to confirm the im-pact of different cryoprotectors on minimization of ascorbic acid losses during freezing and frozen storage of berries. Black currant, guelder, and cranberries in fresh, frozen and de-frosted states were researched in this article. The traditional me-thods to freeze the berries had proved the well-known fact of the significant losses of ascorbic acid. The latter made up 16.8 to 26.3 percents in frozen products and 55.6 to 71.0 percents in those de-frosted. This was the result of cryogenous damages of berries’ cells by ice crystals, and thereinafter the cause of ascorbic acid oxidation by oxidoreductases and its leakage together with cellular juice du-ring berries’ defrosting.The berries processed with cryprotective solutions before free-zing were believed to keep the holity of their structure during free-zing, long-term (for 12 months) frozen storage, and defrosting. Therefore, the effect of ascorbic acid retention in most cases ex-ceeded 80 percents, relatively to its amount in fresh raw materials. Thanks to protective action of cryoprotectors at the stage of berries freezing, the ascorbic acid losses did not overcome 16.8 to 26.3 percents; after frozen storage for 12 months and defrosting, the residual amount of ascorbic acid made up 62.8 to 83.5 percents. Meanwhile, the control samples (berries frozen without protectors) had got ascorbic acid left on the level of 22.4 to 33.6 percents. Realization of theoretical knowledge in studying the cryopro-tectors by cryobiology scientists had shown the positive effect of cryoprotection in berries freezing.
Keywords: технологія оздоровчих продуктів; кафедра іноземних мов професійного спрямування; заморожування; кріопротектори; дефростація; berries; freezing; cryoprotectors; defrosting; ягоди